Analisis Framming Pemberitaan Pilkada DKI Jakarta Tahun 2017 di Surat Kabar Harian Media Indonesia (Unnes Political Science Journal, 2022)
Surya Paloh as the owner of the daily newspaper Media Indonesia, who is also the chairman of the National Democratic Party (Nasdem) has a major influence on news production in Media Indonesia. Regarding the support of the Nasdem party for the Basuki-Djarot pair in the 2017 DKI Jakarta Pilkada, of course, it has implications for the direction of Media Indonesia reporting which seeks to elevate the pair's political image amidst the issue of SARA that blew during the 2017 DKI Pilkada campaign. This is certainly not followed by the vision that Media Indonesia has, namely "Becoming an Innovative, Straightforward, Reliable, and Most Influential Independent Newspaper". Because in reality, Media Indonesia does not carry out an independent function, namely maintaining the attitude of non-participants. This study used a qualitative method. This study conducted in Jakarta. The data was taken from Media Indonesia news text. The data technique used documentation. The data analysis technique used the Zhongdang Pan and Gerald M. Kosicki framing analysis techniques. The data analysis begins with studying data, data reduction, data presentation, and drawing or levers. This study showed that: news framing of the 2017 DKI Jakarta Regional Election in Media Indonesiais carried out by selecting news sources, selecting quotations from news sources, and placing images and idioms that support the news framing. The influence of media owners has an impact on the alignments of media coverage. This shows that media neutrality and objectivity are influenced by media owners. Suggestions from researchers are: media owners should not use their interests in producing news, and provide transparency in the presentation of the news that is displayed. People should be more observant in choosing and digesting messages conveyed in news.